MORAL COMPETENCY OF GRADE 8 AND 9 STUDENTS - Augškalne, Inese; Garjāne, Beatrise (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Sustainability of society demands diversified and balanced development of one’s personality with morality-based quality of knowledge and skills. This can be achieved by respecting the mission of education, namely, to facilitate integrity of social and personal competencies. The goal of the study is to highlight the understanding of teachers and parents about ethical views and moral competency of the young people. The article reveals views of teenagers about values of people and life, about human beings and their obligations. The study combined the quantitative and qualitative research methods, and included content analysis of research documents, surveys and data of pedagogical observations. Moral opinions expressed by the students in the framework of the study reveal that their views on human beings, their obligations towards themselves and society are superficial and declarative. Knowledge about morality and values is notional; therefore, it does not act as motivation for civic action. Moral competency, which is based on relativism, is not complete.